Experiments in the design field – reflections about the research line Design: materials, processes and technologies, from the Post-Graduate Program in Design at UFMA - Rodrigues, Pedro Paulo Bezerra; Noronha , Raquel Gomes (DAT Journal, 2021)
This paper presents recent studies from the research line Design: Materials, Processes and Technology, which is part of the Design Masters Degree course in the Post-Graduate Program in Design at the Federal University of Maranhão – UFMA. The researches shown here have in common the realization of design experiments, which differ from the classic definition of scientific experiment and approach the precepts of design research, supported by participatory design and the practices of design an- thropology, in order to bring research subjects closer together, understanding them as co-researchers. Three studies were reviewed and their analysis contributes to the understanding of the possibilities and frontiers of the experimental method of design.